In vitro study of effect of gold nanoparticles conjugated with triptorelin peptide on the radiosensitivity of breast cancer cells (MCF-7) - Elham Tavakkoli; Seyyed Mohammad Hashemi; Alireza Montazerabadi; Sara Khademi; Farzaneh Ghorbani; Sheyda Mohammadzadeh; Hosein Azimian (Discover Oncology)
Abstract Introduction One of the significant challenges in the field of radiation therapy for cancer cells is the damage to healthy tissues in the vicinity of the tumor. In light of the recent developments in nanotechnology, as well as the historical use of materials with high atomic number to enhance contrast in medical imaging, a potential solution was proposed: the use of targeted gold nanoparticles in conjunction with the triptorelin peptide to enhance the radiation sensitivity of MCF-7 cancer cells. Consequently, due to the presence of the triptorelin peptide receptor on the surface of MCF-7 cells, the nanoparticles are absorbed by the target cells in a targeted manner. By increasing the interaction between the nanoparticles and X-ray MeV 6, it was anticipated that there will be an increase in cell death and optimization of the treatment quality. Methodology Following synthesis and combination with triptorelin peptide, gold nanoparticles coated with alginate were subjected to characterization tests. Subsequently, MTT and colony tests were conducted to ascertain the toxicity of the nanoparticles and the optimal dosage of the drug for use on MCF-7 cells. Subsequently, the cells were subjected to the colony assay to ascertain the level of radiation sensitivity. Following the culturing and treatment of the cells with a concentration of 20 μg/ml of nanoparticles, they were subjected to 2, 4, 6, and 8 Gy (Gray) of radiation. Following the incubation period, the resulting colonies were stained and counted. Finally, the flow cytometry test was employed by Annexin V PI kit to determine the extent of cell death caused by apoptosis. Results The toxicity test finally indicated that a concentration of 20 μg/ml should be employed in the continuation of the study. The results of the colony assay, which was conducted to determine radiation sensitivity, revealed a dose enhancement factor (DEF) of 1.68, 2.32, 1.76 and 1.86, respectively, for radiation doses of 2, 4, 6 and 8 Gy. These findings were observed in the group that received the targeted nanoparticle in conjunction with radiation therapy, when compared to the group that received only radiation therapy. Additionally, the flow cytometry test yielded a synergistic effect of 5.63. The administration of gold nanoparticles in both forms was observed to result in a reduction in cell survival. However, the radio-sensitizing effect of targeted gold nanoparticles with triptorelin peptide was greater, which can be attributed to enhanced cellular uptake by breast cancer cells (MCF-7). Au-Triptorelin nanoparticles with their specific targeting increased radiosensitivity and increased apoptosis compared to the group that only received radiation. Conclusion The results of the tests showed that Triptorelin-AuNPs nanoparticles have the ability to cause targeted sensitivity in MCF-7 cells with triptorelin peptide receptors.